An Intelligent Weather System for Outdoor Clothes Drying - Norizan, Noor Arissa Farhanah; Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2025)
This project introduces an Intelligent Weather System designed to automate the outdoor clothes drying process, especially in tropical climates like Malaysia, where rain is frequent and unpredictable. The system utilizes an ESP32 microcontroller, rain sensor, and servo motor to detect rain and respond automatically by covering the clothes rack. Integrated with the Blynk IoT platform, users receive real-time updates and control options via a smartphone. Testing showed the system worked well in simulation and individual component tests, although the physical prototype faced power issues. This project demonstrates the potential of automation and IoT in household applications, offering convenience and protection against unexpected weather.